Studying the Atuel River sub-basin (Argentina) from a critical physical geography - Langhoff, María Laura (2024)
The paper presents the possibilities offered by the incorporation of critical physical geography (CFG) approaches in the study of water and its circulation. CFG is a line that is being developed with important studies in New Zealand, Canada, Brazil and Chile, in a framework of global socio-environmental crisis where biophysical and physical processes have a decisive intervention of society. Society, through production systems and power networks, contributes to the modeling of the natural environment in irreversible ways, altering geoforms, water systems, climate and soil. This field of research offers instruments that, through disciplinary exchange, can be used to study the complex networks in which water circulates and how water territorialities are constituted. In this way, the concepts of hydro-social cycle (CHS) and hydro-social territory (THS), generated from the intertwining of CFM and the political ecology of water (PE), are elaborated. This paper presents the application of both instrumental concepts to the study of the Atuel River sub-basin in Argentina and the results obtained.